1995
DOI: 10.1111/j.1538-4632.1995.tb00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of the Distribution of Points on a Network

Abstract: This paper shows four statistical methods that examine the distribution of points on a network (such as the distribution of retail stores along streets). The first statistical method is an extension of the nearest-neighbor distance method (the Clark-Evans statistic) defined on a plane to the method defined on a network. The second statistical method examines the efect of categorical attribute values of links (say, types of streets) on the distribution of activity points on a network. The third statistical meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 8 publications
(7 reference statements)
0
38
0
Order By: Relevance
“…Statistical properties of random fields on a network are summarized in [78]. Recently, several spatial statistics, such as spatial autocorrelation, K-function, and Kriging, have been generalized to spatial networks [79][80][81]. Little research has been done on spatiotemporal statistics on the network space.…”
Section: Spatial Statistics For Different Types Of Spatial Datamentioning
confidence: 99%
“…Statistical properties of random fields on a network are summarized in [78]. Recently, several spatial statistics, such as spatial autocorrelation, K-function, and Kriging, have been generalized to spatial networks [79][80][81]. Little research has been done on spatiotemporal statistics on the network space.…”
Section: Spatial Statistics For Different Types Of Spatial Datamentioning
confidence: 99%
“…It is an algorithm for decomposing a circuit-type network into a tree starting from a pole, or a root, and is based on the concept of shortest-distance paths. Later, Okabe, Yomono, and Kitamura (1995) and Okabe and Okunuki (2001) proposed a more refined computational algorithm for constructing such trees and defined it the extended shortest-path tree. They use links that extend from end-nodes of the shortest-path tree until they cover the entire links.…”
Section: Flexible Extended Shortest-path Treementioning
confidence: 99%
“…They use links that extend from end-nodes of the shortest-path tree until they cover the entire links. When the entire network is covered by the extended tree, two end-nodes extending from the opposite ends meet at a single point, which was called an indifferent point by Chorley and Haggett (1967) and a collision point by Okabe, Yomono, and Kitamura (1995). In other words, there exist multiple, mostly two, alternative shortest-path distance routes of equidistance from the root to the collision point.…”
Section: Flexible Extended Shortest-path Treementioning
confidence: 99%
“…However, although the KDE has shown acceptable properties using density values, its homogeneous 2D assumption for events distributed in 1.5D space, such as TC on a road network, seems to be irrelevant [33][34][35][36][37][38]. To overcome this limitation, Okabe proposed the idea of the spatial analysis based on a network, Network-Constrained Kernel Density Estimation (NKDE), which can overcome the shortcomings of the KDE method and reduce the deviation of its results [39][40][41]. Furthermore, research has demonstrated the validity of NKDE to analyze network-based phenomena, such as TC [35,[42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%